Understanding the effects of homeownership and regional unemployment levels on internal migration during the economic crisis in Spain. Issue 4 (2nd April 2020) - Palomares-Linares, Isabel; van Ham, Maarten
ABSTRACT: This paper seeks to understand better the effects of homeownership and regional unemployment levels on inter-provincial migration during the recent economic crisis in Spain. It uses rich individual-level microdata from the last two Spanish censuses (2001–2011) to study migration. The findings suggest that regional unemployment levels do not have a strong impact on internal migration in the period analyzed. However, homeownership is a key explanatory factor of immobility, which became more important in 2011 compared with 2001. This immobility effect of homeownership is stronger in depressed regions, which suggests that some people may be trapped in their dwellings, or the security of homeownership becomes essential when the structural conditions are unfavourable.